SP0180 Health professionals workshop session: "I've been asked to review a clinical guideline – where do I start?". (23rd January 2014) - Stoffer, M.; van Bodegom-Vos, L.; Lund, H.; Vliet Vlieland, T.
Abstract : The number of Clinical Guidelines (CG) is constantly increasing and the quality of CGs differs largely. For this reason, a critical appraisal with standardized instruments is important. The aims of this appraisal are to determine the quality of CGs and to ensure that those with the highest quality will be disseminated and implemented. An appropriate international standard for assessing the methodological quality of CGs represents the "Appraisal of Guidelines for Research and Evaluation (AGREE II) Instrument" (www.agreetrust.org ). Part of the workshop will be an introduction to the AGREE II Instrument as well as a practical exercise on the AGREE II Instrument including a plenary discussion of the results. Disclosure of Interest: None Declared